A Global Humanities Approach to the United Nations' Sustainable Development Goals Understanding Planet, People, and Prosperity - Comfort, Kelly (Taylor & Francis, 2024)
Cowspiracy; Environment and sustainability; Environmental humanities; SDGs; Sustainable Development Goals;Teaching Sustainability; The White tiger